Estrutura florestal, serrapilheira e atributos do solo em borda de Floresta Tropical com manejo de trepadeiras por seis anos - Barboza, Patrick Ricardo Cândido Gonçalves (2023)
The Vassununga State Park (PEV), in the municipality of Santa Rita do Passa Quatro - SP, is a State Conservation Unit, possessing vast diversity in fauna and flora, composed of formations of Atlantic Forest (Semideciduous Seasonal Forest) and Cerrado, characterized as a transition area between these biomes. Its stratified composition in several plots and history of exogenous disturbances have propitiated an increase in the population of vines. In this work, we evaluated possible changes in forest structure, litterfall and soil chemical attributes of semideciduous seasonal forest in edge areas after six years of management by annual cutting of vines. Twenty-seven (10x10m) plots were marked near the edge, 14 of them in areas that did not receive any management, control (C), and another 13 that underwent an annual vine cutting (M) during the dry season. Samples of literfall and soil were collected to assess differences in dry mass and soil chemical attributes. Forest and literfall structure did not differ significantly in managed and unmanaged plots. However, it was possible to verify chemical changes in the managed soil, such as doubled Al content (from 4.9 mmolc/dm3 to 9 mmolc/dm3), lower pH (from 4.7 to 4.5), and lower organic matter content (~10%), suggesting a change soil.